Improving the therapeutic efficacy of neural progenitor cell transplantation following spinal cord injury - Lane, Michael A. (Expert Rev Neurother, 2016)
INTRODUCTION: There have been a wide range of preclinical studies testing cellular therapies to repair the injured spinal cord, yet they remain a challenge to translate because of inconsistencies in efficacy, limited number of patients with acute/subacute SCI and the high costs of clinical trials. AREA COVERED: This paper focusses on the therapeutic potential of neural precursor cells (NPCs) because they can provide the cellular components capable of promoting repair and enhancing functional improvement following spinal cord injury (SCI). The authors discuss the challenges of NPC transplantation with respect to different populations of NPCs of glial and neuronal lineages, the timing of treatment relative to acute and chronic injury, and the progress in ongoing clinical trials. EXPERT COMMENTARY: Preclinical research will continue to elucidate mechanisms of recovery associated with NPC transplants, including increasing the partnership with related fields such as spinal atrophies and multiple sclerosis. The clinical trials landscape will grow and include both acute and chronic SCI with increased partnership and strengthened communication between biotechnology, government and academia. There will also be growing effort to develop better biomarkers, imaging and outcome measures for detailed assessment of neurological function and measures of quality of life.